2002
DOI: 10.5483/bmbrep.2002.35.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Collagenolytic Protease from the Filefish, Novoden modestrus

Abstract: A serine collagenolytic protease was purified from the internal organs of filefish, Novoden modestrus, by ammonium sulfate, ion-exchange chromatography on a DEAE-Sephadex A-50, ion-exchange rechromatography on a DEAE-Sephadex A-50, and gel filtration on a Sephadex G-150 column. The molecular mass of the filefish serine collagenase was estimated to be 27.0 kDa by gel filtration and SDS-PAGE. The purified collagenase was optimally active at pH 7.0-8.0 and 55 o C. The purified enzyme was rich in Ala, Ser, Leu, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
39
0
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 29 publications
11
39
0
8
Order By: Relevance
“…In relation to the susceptibility to metal ions, the data obtained from our study corroborate those reported by KIM et al (2002) andWU et al (2010a) which observed increased activity of collagenolytic proteases of filefish N. modestrus and sea bream P. major when exposed to the ions Ca 2+ and Mg 2+ , respectively. HAYET et al (2011) .…”
Section: Sensitivity Of the Collagenolytic Enzymes To Metal Ions And supporting
confidence: 81%
See 4 more Smart Citations
“…In relation to the susceptibility to metal ions, the data obtained from our study corroborate those reported by KIM et al (2002) andWU et al (2010a) which observed increased activity of collagenolytic proteases of filefish N. modestrus and sea bream P. major when exposed to the ions Ca 2+ and Mg 2+ , respectively. HAYET et al (2011) .…”
Section: Sensitivity Of the Collagenolytic Enzymes To Metal Ions And supporting
confidence: 81%
“…The abundance of type V is low, but it is found to be associated with types I and II, bone and cartilage, and other tissues, with important participation in the function of tensile strength (DABOOR et al, 2010). LIMA et al (2013) observed that the cleavage of type I collagen by collagenase produced by Penicillium aurantiogriseum, was similar to those already described with aquatic organisms KIM et al, 2002;DABOOR et al, 2012). According to HERREIRO-HERNANDEZ et al (2002), once one collagenolytic enzyme works degrading particular collagen types, it is likely that other proteases may follow the process.…”
Section: Hydrolysis Of Collagen By the Collagenolytic Enzymementioning
confidence: 64%
See 3 more Smart Citations